FAKTOR - FAKTOR YANG MEMPENGARUHI MINAT KONSUMEN DALAM MENGGUNAKAN JASA TRANSPORTASI KRL / COMMUTER LINE DENGAN METODE ANALISIS FAKTOR - Besse Arnawisuda Ningsi; Ani Putriyani (Program Studi Matematika FMIPA Universitas Pamulang, 2019)
The purpose of this study was to find out how many factors were formed through the reduction process, to determine which factors most dominantly influence consumer interest in using KRL Commuter Line transportation services, to find out how much influence the most dominant factors influence consumer interest in using KRL Commuter transportation services Line. In this study, the Factor Analysis method was used with principal component analysis techniques using SPSS software. 7 stages of factor analysis, namely: (1) formulating a problem, (2) Variable Interference Test, (3) forming a correlation matrix, (4) determining factor analysis methods, (5) extracting factors, (6) rotating factors, and (7) interpret factors. Based on the results of the study, the number of factors formed from the reduction process is 7 factors. Consisting of one factor (F1) with a correlation value of 0.608, factor two (F2) with a correlation value of -0.277, factor three (F3) with a correlation value of -0.246, factor four (F4) with a correlation value of 0.419, factor five (F5) with the correlation value is 0.716, factor six (F6) with a correlation value of -0.392, factor seven (F7) with a correlation value of 0.570. The most dominant factor affecting consumer interest in using KRL Commuter Line transportation services is factor five (F5) with a correlation value of 0.716 or 71.6%.